Pulmonary Function Test in Construction Workers and a Referent Food Industry Group: A Comparative Study - touraj khazraee; zahra zamanian; rezvan zare; farzaneh mobasheri (Fasa University of Medical Sciences, 2015)
Background & Objectives: Almost 9 to 12% of construction workers are exposed to dust in their workplace. However, few studies have assessed the risks and complications of this exposure. This study aims to evaluate the pulmonary effects of construction workers' occupational exposure to dust. Materials & Methods: This cross-sectional study was conducted in the southeast of Fars province. In this research a total of 50 construction workers and 50 referent workers from a food industry were studied. From each individual the data of spirometric parameters and related factors (age, weight, history of lung disease, and smoking) were collected. These data were analyzed via independent sample t test, Chi-square test, logistic regression, and Pearson correlation using SPSS16 software. Results: This study showed that the means of FVC and FEV1 in construction workers were significantly higher than those of food industry workers (p= 0/008 and p < 0/0001, respectively). However, the Odds Ratio of  abnormal spirometry pattern showed no significant difference between two groups. Between the spirometric parameters, only the FEV1 / FVC ratio had a significant positive correlation with age. This correlation was equal in both groups (r ~ 0/3 and p < 0/05). Conclusion: The findings of this study provide evidence to support the proposition that construction workers are not at risk of developing respiratory disorders.